Recognition and commemoration of Tadeusz Kościuszko in American socjety in the context of contemporary US–Poland relations - Gradowski, Aleksander (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
When talking about people who influence the shaping of Polish-American relations, one of the first characters to come to mind is without a shadow of doubt Tadeusz Kościuszko. The purpose of the following paper is to discuss the most important factors that allowed the creation of the legend of Tadeusz Kościuszko in the United States, and to illustrate to what extent Tadeusz Kościuszko’s person is commemorated and recognized among the American population. The purpose of this paper is also to answer the questions, what is his role in public discourse and Polish-American diplomacy, as well as what role does his character play in the functioning of the Polish community in the United States. The work was based on the historical research method. In the course of its creation, monographs, press articles, and internet sources in Polish and English were used. The subject of the research is determining Tadeusz Kościuszko’s recognition, description of all issues related to commemorating him, as well as emphasizing the importance of his character for mutual relations between Poland and the United States, both in matters concerning diplomatic aspects and all social feelings manifested in both nations to each other.